Tensile Properties of Angle Cured Laminated Composites Structures under Gravity Effects - Yuhazri, M.Y.; Jennise, T.T.T.; Sihombing, H.; M. Radzai , Said; Nirmal, U.; Megat Ahmad, M.M.H. (Trans Tech Publications, Switzerland, 2013)
As the usage of composites materials are significant in the industries of automobiles,shipping and constructions due to their non-corrosive and high strength to weight ratio. Anyway, the production of composites needed to be increased to meet the demand. At this stage, problem faced by Small and Medium Industries / Entrepreneurs (SMI/E) is the confined and limited space available that restricts the optimum productivity. They commonly cure the composites horizontally that requires ample space and unable to afford for high-end equipment such as mechanical oven and autoclave in the production as a result of high capital cost.This research is carried out to study the feasibility of the gravity effects on curing position of the laminated composite structures to enhance the curing space needed. The aim of the research was to investigate the tensile properties of the thermosetting laminated composite by curing the laminate at different angle using vacuum bagging technique. From the testing, SN 5 which denominated to be 60˚ found to have the best tensile properties in term of maximum force exerted and Young’s modulus.